THE IMPACT OF PSYCHOANALYSIS ON MODERN PSYCHOTHERAPY - Chorna, Olena (Personality and environmental issues, 2023)
The article is devoted to a comprehensive analysis of the influence of psychoanalysis on the formation and development of modern psychotherapy. The author explores the evolution of psychoanalytic theory from the classical positions of S. Freud to modern psychodynamic approaches, paying attention to the transformation of key concepts, techniques and formats of therapeutic work. The work emphasizes the combination of the psychoanalytic paradigm with other areas of psychotherapy (cognitive-behavioral, humanistic, art therapy, interpersonal and family approaches), which has become especially relevant in the context of modern social challenges – the COVID-19 pandemic, war, mass psychotraumas. The study uses an interdisciplinary approach that combines theoretical analysis, a review of evidence-based studies (RCTs, meta-analyses), and an analysis of empirical data obtained in the Ukrainian context. The results of the adaptation of psychoanalytic practice to new conditions (online environment, group formats, short-term interventions) are presented, in particular in work with veterans, children with special educational needs, and victims of war trauma. Particular attention is paid to such psychoanalytic concepts as transference, countertransference, defense mechanisms, symbolization and emotional regulation, which retain their relevance in the therapeutic process. The article emphasizes the need to adapt psychoanalytic care to the cultural and social context, as well as the importance of professional training of therapists to work in conditions of high psycho-emotional stress. The results of the study confirm that psychoanalysis has not only not lost its relevance, but has also been integrated into modern psychotherapy as a deep, flexible and scientifically based approach that can effectively respond to new social demands.